(untitled) (REMUNOM, 2025)
The indiscriminate use of GLP‑1 receptor agonists—such as semaglutide and liraglutide—originally developed to treat type 2 diabetes and obesity, has raised significant health concerns when used for aesthetic weight loss purposes without medical supervision. While these medications can lead to substantial weight loss, they are associated with common side effects like nausea, vomiting, diarrhea, and constipation. More serious risks include pancreatitis, gastroparesis, and intestinal obstruction. Additionally, rapid weight loss can result in muscle mass loss, particularly in individuals who do not engage in resistance exercises or consume adequate protein, potentially leading to osteoporosis. The unregulated use of these drugs has led to shortages, affecting patients who genuinely need them for medical conditions. Moreover, the promotion of such medications for aesthetic purposes can reinforce harmful beauty standards and stigmatize diverse body types. It’s crucial that GLP‑1 receptor agonists be used only under medical supervision to ensure safety and efficacy.